ITIL® 4 High-velocity IT (HVIT) your companion to the ITIL 4 Managing Professional HVIT certification - Agutter, Claire (IT Governance Publishing Ltd, 2021)
An excellent supplement to any ITIL 4 High-velocity IT training course. ITIL® 4 High-velocity IT (HVIT) - Your companion to the ITIL 4 Managing Professional HVIT certification is a study guide designed to help students pass the ITIL® 4 High-velocity IT module.